ANALISIS SISTEM PERTAMBANGAN BITCOIN DAN LITECOIN MENGGUNAKAN METODE PEMBAYARAN CRYPTOCURRENCY - M. Abdul Alim Alami; Suwanto Raharjo; Uning Lestari (Jurnal SCRIPT, 2015)
Cryptocurrency is a method used payment method transaction buying and selling on the internet. Just as the currency used as means of payment in general.There are various types of cryptocurrency used to process payment transactions among other types of bitcoin and litecoin. Cryptocurrency types of bitcoin and litecoin made by using the security of science cryptography. Bitcoin and litecoin generated through the mining process that uses specialized hardware cryptocurrency mining. This analysis to determine system mining bitcoin and litecoin by mining bitcoin and litecoin. Mining bitcoin and litecoin process by mining pool. Mining pool is mining services provider cyrptocurrency by the miner. The analysis is performed on five probation and litecoin bitcoin mining for three days the mining process is performed to determine the difference bitcoin and litecoin. Results of bitcoin mining and litecoin cryptocurrency types can be used as a method to process payment transactions of buying and selling on the internet. Bitcoin and litecoin can also exchange currency types rupiah or dollars.